(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Enterprise Resource Planning (ERP) is one of the hottest subjects in the business world today, huge amounts of money is invested in ERP projects, and in them many organizations see opportunities for costs savings and/or competitive advantage due to their all-embracing nature, ERP systems may have far reaching consequences for any enterprise. In view of the above analysis it can be inferred that ERP implementation has been a challenging task worldwide and India is no exception in this regard. The current paper is designed to cover the issues of ERP application in the Public & Private sector industries in the Bundelkhand region a state in the making comprising districts of Uttar Pradesh & Madhya Pradesh states of India. The paper tries to highlight ERP (Enterprise Resource Planning) in PPSI (Public & Private Sector Industries) in Bundelkhand region.